Effects of A One-week Fasting Therapy in Patients with Type-2 Diabetes Mellitus and Metabolic Syndrome – A Randomized Controlled Explorative Study - Li, Chenying; Sadraie, Badri; Steckhan, Nico; Kessler, Christian; Stange, Rainer; Jeitler, Michael; Michalsen, Andreas (Experimental and Clinical Endocrinology & Diabetes, 2017)
There is increasing experimental evidence for beneficial effects of calorie restriction and intermittent fasting in type 2 diabetes mellitus (T2DM). In humans, prolonged fasting is established as a health-promoting complementary treatment in Europe and claimed to improve metabolism by a complex hormetic response. We aimed to investigate effects of a one-week fasting period compared to usual care in T2DM by means of a pilot trial. Patients with manifest T2DM medically treated with oral hypoglycemic agents and/or insulin were randomly assigned to a 7-day fasting program followed by dietary advice or to usual care and dietary advice only. Fasting was performed according to the method of Buchinger with a nutritional energy intake of 300kcal/day by liquids only and stepwise re-introduction of solid food thereafter. Outcomes were assessed baseline and after 4 months. Of 46 enrolled participants, 32 (n=16 each group) completed the trial and were included for final analyses. Fasting was well accepted, there were no serious adverse events. After 4 months mean weight decreased by 3.5 kg and 2.0 kg in the fasting vs. control group (p=0.03) paralleled by greater reduction of abdominal circumference (p=0.001). Fasting led to a significant decrease of systolic/diastolic blood pressure (p=0.01; p=0.003) and increased quality-of-life (p=0.04), while for HbA1c, insulin and HOMA-index only non-significant improvements were observed. Results of this study suggest that prolonged fasting is feasible and might have beneficial clinical effects. The effectiveness of fasting should be proved in larger confirmatory trials that include intermittent fasting in follow-ups to enable more pronounced and long-term effects.
Keywords: calorie restriction; type 2 diabetes mellitus; fasting; trial